Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the antiderivatives of the function [tex]\( f(y) = -\frac{28}{y^{29}} \)[/tex], let's proceed as follows:
1. Identify the function:
[tex]\[ f(y) = -\frac{28}{y^{29}} \][/tex]
2. Rewrite using exponents:
We can rewrite the function with a negative exponent for ease of integration:
[tex]\[ f(y) = -28 y^{-29} \][/tex]
3. Apply the power rule for integration:
The power rule for integration states that if [tex]\( f(y) = y^n \)[/tex], then the antiderivative [tex]\( F(y) \)[/tex] is given by:
[tex]\[ \int y^n \, dy = \frac{y^{n+1}}{n+1} + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
4. Integrate the function:
In our case, [tex]\( n = -29 \)[/tex]. Applying the power rule:
[tex]\[ \int -28 y^{-29} \, dy = -28 \int y^{-29} \, dy \][/tex]
[tex]\[ = -28 \left( \frac{y^{-29+1}}{-29+1} \right) + C \][/tex]
Simplify the exponent and the denominator:
[tex]\[ = -28 \left( \frac{y^{-28}}{-28} \right) + C \][/tex]
[tex]\[ = -28 \left( \frac{y^{-28}}{-28} \right) + C \][/tex]
5. Simplify the expression:
The [tex]\(-28\)[/tex] in the numerator and denominator cancels out:
[tex]\[ = y^{-28} + C \][/tex]
Therefore, the antiderivatives of [tex]\( f(y) = -\frac{28}{y^{29}} \)[/tex] are:
[tex]\[ F(y) = y^{-28} + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
1. Identify the function:
[tex]\[ f(y) = -\frac{28}{y^{29}} \][/tex]
2. Rewrite using exponents:
We can rewrite the function with a negative exponent for ease of integration:
[tex]\[ f(y) = -28 y^{-29} \][/tex]
3. Apply the power rule for integration:
The power rule for integration states that if [tex]\( f(y) = y^n \)[/tex], then the antiderivative [tex]\( F(y) \)[/tex] is given by:
[tex]\[ \int y^n \, dy = \frac{y^{n+1}}{n+1} + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
4. Integrate the function:
In our case, [tex]\( n = -29 \)[/tex]. Applying the power rule:
[tex]\[ \int -28 y^{-29} \, dy = -28 \int y^{-29} \, dy \][/tex]
[tex]\[ = -28 \left( \frac{y^{-29+1}}{-29+1} \right) + C \][/tex]
Simplify the exponent and the denominator:
[tex]\[ = -28 \left( \frac{y^{-28}}{-28} \right) + C \][/tex]
[tex]\[ = -28 \left( \frac{y^{-28}}{-28} \right) + C \][/tex]
5. Simplify the expression:
The [tex]\(-28\)[/tex] in the numerator and denominator cancels out:
[tex]\[ = y^{-28} + C \][/tex]
Therefore, the antiderivatives of [tex]\( f(y) = -\frac{28}{y^{29}} \)[/tex] are:
[tex]\[ F(y) = y^{-28} + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.